Answer:
124
Step-by-step explanation:
Answer:
THANK YOU! YOU TOO! :)
Step-by-step explanation:
Have a nice dayyyyyy <3
Answer:
x-int: (3, 0)
y-int: (0, 2)
Step-by-step explanation:
The x-int is found when y = 0. Set <em>y</em> to 0 to solve for the x-int.
The y-int is found when x = 0. Set <em>x</em> equal to 0 to solve for the y-int.
Answer : C
we need to the value of f(–1)
Table is given in the question
From the table ,
f(x) = 4 when x= -5, that is f(-5) = 4
f(x) = 0 when x= -1, that is f(-1) =0
f(x)= -1 when x=6, that is f(6) = -1
f(x)= -3 when x=9, that is f(9) = -3
So, the value of f(–1) = 0
Answer:
The first one
Step-by-step explanation: